Population-Based Study of the Clinical Characteristics and Risk Factors of Ischemic Colitis - Wu, Xiaxia; Bao, Zhijun (Turkish Journal of Gastroenterology, 2021)
Background: Ischemic colitis (IC) is a common ischemic disorder of the colon caused by insufficient blood supply to the colonic mucosa. This study aimed to identify the clinical characteristics, comorbidities, and risk factors in patients with IC. Methods: We performed a retrospective population-based study using electron video-colonoscopy imaging and pathological biopsies from 168 patients diagnosed with IC. A retrospective controlled study was used to analyze differences between a young to middle-aged patient group (78 cases) and an elderly patient group (90 cases) on the basis of clinical characteristics and risk factors. Results: The primary symptoms in the 168 patients with IC were abdominal pain, diarrhea, and hematochezia. White blood cells (WBC), neutrophilic granulocyte percentage (NEUT%), C-reactive protein (CRP), and D-dimer were significantly elevated in elderly patients. The sigmoid colon and descending colon were the most common lesion locations (57.1% and 33.9%, respectively). Hypertension, cerebral infarction, and coronary heart disease were the most common comorbidities in elderly patients, while smoking history was the most common risk factor in young to middle-aged patients. Conclusion: The sigmoid colon and descending colon are the most affected locations in IC. Hypertension, diabetes mellitus, and cerebral infarction are the most common risk factors and comorbidities.